Chronic cerebrovascular dysfunction after traumatic brain injury. Issue 7 (27th April 2016) - Jullienne, Amandine; Obenaus, Andre; Ichkova, Aleksandra; Savona‐Baron, Catherine; Pearce, William J.; Badaut, Jerome
Abstract : Traumatic brain injuries (TBI) often involve vascular dysfunction that leads to long‐term alterations in physiological and cognitive functions of the brain. Indeed, all the cells that form blood vessels and that are involved in maintaining their proper function can be altered by TBI. This Review focuses on the different types of cerebrovascular dysfunction that occur after TBI, including cerebral blood flow alterations, autoregulation impairments, subarachnoid hemorrhage, vasospasms, blood–brain barrier disruption, and edema formation. We also discuss the mechanisms that mediate these dysfunctions, focusing on the cellular components of cerebral blood vessels (endothelial cells, smooth muscle cells, astrocytes, pericytes, perivascular nerves) and their known and potential roles in the secondary injury cascade. © 2016 Wiley Periodicals, Inc. Abstract : Traumatic brain injuries lead to alteration of cerebrovascular function by inducing decreased cerebral blood flow, impaired autoregulation, subarachnoid hemorrhage, vasospasms, edema, blood–brain barrier disruption, and long‐term neurodegeneration. The roles of endothelial cells, smooth muscle cells, astrocytes, and perivascular innervation in these injury cascades are discussed in this Review.